Dental Restorative Materials Based on Thiol-Michael Photopolymerization - Huang, S. (J Dent Res, 2018)
Step-growth thiol-Michael photopolymerizable resins, constituting an alternative chemistry to the current methacrylate-based chain-growth polymerizations, were developed and evaluated for use as dental restorative materials. The beneficial features inherent to anion-mediated thiol-Michael polymerizations were explored, such as rapid photocuring, low stress generation, ester content tunability, and improved mechanical performance in a moist environment. An ester-free tetrafunctional thiol and a ultraviolet-sensitive photobase generator were implemented to facilitate thiol-Michael photopolymerization. Thiol-Michael resins of varied ester content were fabricated under suitable light activation. Polymerization kinetics and shrinkage stress were determined with Fourier-transform infrared spectroscopy coupled with tensometery measurements. Thermomechanical properties of new materials were evaluated by dynamic mechanical analysis and in 3-point bending stress-strain experiments. Photopolymerization kinetics, polymerization shrinkage stress, glass transition temperature, flexural modulus, flexural toughness, and water sorption/solubility were compared between different thiol-Michael systems and the BisGMA/TEGDMA control. Furthermore, the mechanical performance of 2 thiol-Michael composites and a control composite were compared before and after extensive conditioning in water. All photobase-catalyzed thiol-Michael polymerization matrices achieved >90% conversion with a dramatic reduction in shrinkage stress as compared with the unfilled dimethacrylate control. One prototype of ester-free thiol-Michael formulations had significantly better water uptake properties than the BisGMA/TEGDMA control system. Although exhibiting relatively lower Young’s modulus and glass transition temperatures, highly uniform thiol-Michael materials achieved much higher toughness than the BisGMA/TEGDMA control. Moreover, low-ester thiol-Michael composite systems show stable mechanical performance even after extensive water treatment. Although further resin/curing methodology optimization is required, the photopolymerized thiol-Michael prototype resins can now be recognized as promising candidates for implementation in composite dental restorative materials.